Polycrystal Cs2ZnI4 material with low thermal conductivity, single crystal Cs2ZnI4 material and application of polycrystal Cs2ZnI4 material and single crystal Cs2ZnI4 material
Through the high-temperature treatment of CsI and ZnI2 and the vertical gradient freezing method, polycrystalline and single-crystalline Cs2ZnI4 materials with low thermal conductivity and high thermal stability were successfully obtained, solving the limitations of existing materials in terms of thermal conductivity and high temperature stability. , achieving lower thermal conductivity and better thermal insulation properties.
Patent Information
- Application Number
- CN202411331691.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-10
AI Technical Summary
The existing low-thermal conductivity materials have limitations in thermal conductivity, processability and high temperature stability. In particular, the study on the low-thermal conductivity characteristics of Cs2ZnI4 materials has not yet been thorough, and the preparation and application of their single crystals have not been reported.
Polycrystalline Cs2ZnI4 material is obtained by melting, quenching and annealing CsI and ZnI2 at high temperature under vacuum environment, and the single crystal Cs2ZnI4 material is grown by vertical gradient freezing method to control its crystal structure and thermal conductivity.
Polycrystalline and single crystal Cs2ZnI4 materials with low thermal conductivity and high thermal stability have a room temperature thermal conductivity of no more than 0.17W/m-1K-1, which has excellent structural stability and anisotropy, and are suitable for use in high temperature environments. , and simplifies the preparation process and is suitable for industrial production.
Smart Images

Figure CN119287511A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of low thermal conductivity materials, and in particular relates to a low thermal conductivity polycrystalline Cs2ZnI4 material, a single crystal Cs2ZnI4 material and applications thereof. Background Art
[0002] With the continuous development of thermoelectric materials, thermal insulation coatings and other thermal management applications, the demand for low thermal conductivity materials is increasing. Currently, low thermal conductivity materials are mostly made of glass, ceramics or polymer composites, but these materials have certain limitations in thermal conductivity, processability and high temperature stability. In order to solve these problems, the development of materials with lower thermal conductivity and higher thermal stability has become an important research direction.
[0003] Cs2ZnI4 is a new type of compound that exhibits extremely low thermal conductivity due to its unique crystal structure and strong ionic bonding. However, current research on Cs2ZnI4 materials mainly focuses on its crystal structure and optical properties, and the preparation and application of single-crystal Cs2ZnI4 materials with low thermal conductivity properties have not been reported.
[0004] Therefore, a preparation method for low thermal conductivity Cs2ZnI4 materials remains to be developed and its potential in low thermal conductivity applications is revealed. Summary of the invention
[0005] The purpose of the present invention is to provide a low thermal conductivity polycrystalline Cs2ZnI4 material, a single crystal Cs2ZnI4 material and applications thereof, so as to obtain a low thermal conductivity Cs2ZnI4 material with low thermal conductivity and high thermal stability.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] The present invention provides a polycrystalline Cs2ZnI4 material with low thermal conductivity, which is prepared by the following method:
[0008] CsI and ZnI2 are mixed and ground evenly, and then high-temperature melting, quenching and annealing are performed in sequence under a vacuum environment to obtain a polycrystalline Cs2ZnI4 material with low thermal conductivity;
[0009] The thermal conductivity of the polycrystalline Cs2ZnI4 material at room temperature is not more than 0.17 W / m -1 K -1 .
[0010] Furthermore, the molar ratio of CsI to ZnI2 is 2:1.
[0011] Furthermore, the purity of the CsI and ZnI2 is ≥99.99%.
[0012] Furthermore, the CsI and ZnI2 are mixed and ground evenly and then transferred into a quartz tube, and the quartz tube is evacuated to <6Pa and then packaged.
[0013] Furthermore, the high temperature melting temperature is 650-700°C, preferably 650°C; the high temperature melting time is 4-6h, preferably 5h.
[0014] Furthermore, the quenching medium is water.
[0015] Furthermore, the annealing temperature is 200-300° C., preferably 250° C.; the annealing time is 24-72 h, preferably 48 h.
[0016] The present invention also provides a single crystal Cs2ZnI4 material with low thermal conductivity, which is prepared by the following method:
[0017] The polycrystalline Cs2ZnI4 material is grown in a vacuum environment by a vertical gradient freezing method to obtain a single crystal Cs2ZnI4 material with low thermal conductivity.
[0018] Vertical Gradient Freeze (VGF) is a mature technology for growing single crystals, especially suitable for growing single crystals with specific crystal orientation and high quality requirements. This method controls the temperature gradient during crystal growth so that the molten material gradually solidifies during the slow cooling process, thus forming a single crystal.
[0019] Furthermore, the specific steps of the vertical gradient freezing method are: sealing the polycrystalline Cs2ZnI4 material in a quartz tube, placing the quartz tube in a vertical temperature gradient furnace, first melting it at high temperature, and then cooling it to room temperature to obtain a single crystal Cs2ZnI4 material.
[0020] Furthermore, the high temperature melting temperature is 650-700°C, preferably 650°C; the high temperature melting time is 4-6h, preferably 5h.
[0021] Furthermore, the cooling rate is 0.4-0.6°C / h.
[0022] Furthermore, the single crystal Cs2ZnI4 material has anisotropy, and its thermal conductivity at room temperature is not greater than 0.17 W / m -1 K -1 The thermal conductivity along the c-axis can be as low as 0.11 W / m -1 K -1 .
[0023] The present invention also provides an application of the polycrystalline Cs2ZnI4 material and the single crystal Cs2ZnI4 material in electronic equipment, thermoelectric materials or aerospace fields. The low thermal conductivity polycrystalline Cs2ZnI4 material and the single crystal Cs2ZnI4 material can be applied to electronic equipment, aerospace and other fields that require strict thermal management, and can be used to prepare thermoelectric materials and thermal insulation coatings.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention successfully prepared polycrystalline Cs2ZnI4 material with low thermal conductivity, and further obtained single crystal Cs2ZnI4 material by vertical gradient freezing method, and the thermal conductivity of polycrystalline Cs2ZnI4 material and single crystal Cs2ZnI4 material at room temperature is no more than 0.17W / m -1 K -1 .
[0026] (2) The Cs2ZnI4 material prepared by the present invention has excellent structural stability and does not undergo phase change or phase decomposition in a wide temperature range (up to 500K). Compared with many existing materials, this material can still maintain its structure and thermal properties at higher temperatures and is suitable for use in high temperature environments without deterioration of material properties due to thermal expansion or phase change.
[0027] (3) The thermal conductivity of the single crystal Cs2ZnI4 material further prepared by the present invention can be as low as 0.11 W / m at room temperature. -1 K -1 , which is lower than most traditional low thermal conductivity materials (such as glass, ceramics, etc.), indicating that it has better performance in thermal insulation.
[0028] (4) The single crystal Cs2ZnI4 material further prepared by the present invention has significant anisotropy, and its thermal conductivity along the c-axis is much lower than that along the a-axis or b-axis. This property is particularly important when designing devices that precisely control the direction of heat flow, and can better achieve thermal management and optimize material performance.
[0029] (5) The preparation method of the low thermal conductivity Cs2ZnI4 material obtained by the present invention is simple, with simple steps and strong controllability, and is suitable for large-scale industrial production.
[0030] (6) The Cs2ZnI4 material prepared in the present invention is composed of relatively non-toxic and sustainably obtained elements (Cs, Zn and I). Compared with some existing low thermal conductivity materials (such as compounds containing heavy metals or rare elements), it is more environmentally friendly and in line with the development trend of green materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 11 is the X-ray diffraction pattern of Cs2ZnI4 powder at different temperatures in Example 1 of the present invention.
[0032] Figure 2 1 is the X-ray diffraction pattern of the Cs2ZnI4 polycrystal and single crystal of Example 1 of the present invention.
[0033] Figure 3 The scanning electron microscope image and element distribution diagram of the Cs2ZnI4 material of Example 1 of the present invention.
[0034] Figure 4 This is an optical crystal image of the single crystal Cs2ZnI4 material of Example 1 of the present invention.
[0035] Figure 5 This is the X-ray photoelectron spectrum of the Cs2ZnI4 material of Example 1 of the present invention.
[0036] Figure 6 This is the electrochemical impedance spectrum of the Cs2ZnI4 material of Example 1 of the present invention.
[0037] Figure 7 This is a temperature-dependent thermal conductivity diagram of the Cs2ZnI4 material of Example 1 of the present invention.
[0038] Figure 8 This is the sound velocity diagram of the Cs2ZnI4 material of Example 1 of the present invention.
[0039] Fig. 9 This is the temperature-dependent Raman spectrum of the Cs2ZnI4 material of Example 1 of the present invention. DETAILED DESCRIPTION
[0040] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0041] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0042] Embodiment 1:
[0043] This embodiment provides a polycrystalline Cs2ZnI4 material and a single crystal Cs2ZnI4 material, and the preparation method thereof is as follows:
[0044] S1: Weigh CsI and ZnI2 with a purity of ≥99.99% according to a stoichiometric ratio of 2:1, put them into a quartz tube, evacuate to less than 6 Pa and then package. Melt at 650°C for 5 hours, then quench with water, anneal at 250°C for 48 hours, and cool to room temperature to obtain a polycrystalline Cs2ZnI4 ingot.
[0045] S2: Single crystal Cs2ZnI4 is grown by vertical gradient freezing method. A sealed quartz tube is placed in a vertical temperature gradient furnace, and the temperature at the tip of the quartz tube (T0) is heated to 650°C, maintained for 5 hours, then reduced to 560°C for 1 hour, and slowly cooled from 560°C to 400°C at a rate of 0.5°C / h, and finally slowly reduced to room temperature to obtain single crystal Cs2ZnI4 material.
[0046] In this example, the Cs2ZnI4 material prepared above is characterized as follows:
[0047] (1) Temperature dependence of Cs2ZnI4 powder by X-ray diffraction (XRD, Rigaku SmartLab, Cu-Kα) Figure 1 As shown, the results show that no phase change or phase decomposition occurs in the range of up to 500K, which proves that the Cs2ZnI4 material prepared in this embodiment can still maintain its structure and thermal properties at higher temperatures and is suitable for use in high temperature environments without deterioration of material properties due to thermal expansion or phase change.
[0048] (2) The orientation of single crystal Cs2ZnI4 was characterized by XRD (DX2000, Cu-Kα), as shown in Figure 2 As shown, by comparing with the known standard diffraction peak peak, we obtain single crystals in three directions of a, b and c.
[0049] (3) The composition of single crystal Cs2ZnI4 was characterized using a scanning electron microscope (SEM, Phenom Pro) equipped with an energy dispersive spectrometer (EDS), such as Figure 3 The typical optical photo of single crystal Cs2ZnI4 is shown in Figure 1. Figure 4 shown.
[0050] (4) The internal valence state of the compound was analyzed by X-ray photoelectron spectroscopy (XPS, Al-Kα radiation) using ESCALAB 250Xi (Thermo Fisher Scientific). By comparing with the known standard peaks, it was determined that the sample contained Cs, Zn, and I elements. The valence state of the sample was determined based on the energy of the characteristic element spin-orbit splitting peak, which was consistent with the compound ratio, once again proving that the preparation was good, such as Figure 5 shown.
[0051] Embodiment 2:
[0052] The present embodiment provides a single crystal Cs2ZnI4 material, and its preparation method is basically the same as that of Example 1, except that the temperature range of the present embodiment is lower. The present embodiment also adopts the vertical gradient freezing method to grow single crystal Cs2ZnI4, specifically, the polycrystalline powder is placed in a quartz tube, and the vacuum is evacuated to less than 6Pa and then packaged. The sealed quartz tube is placed in a vertical temperature gradient furnace, and the temperature (T0) at the tip of the quartz tube is heated to 650°C, maintained for 5h, and then reduced to 500°C for 2h, and slowly cooled from 500°C to 400°C at a rate of 0.7°C / h, and finally slowly reduced to room temperature, and the single crystal Cs2ZnI4 material was also successfully obtained.
[0053] The present invention performs the following performance tests on the Cs2ZnI4 material obtained in Example 1:
[0054] (1) The ionic conductivity of Cs2ZnI4 material was measured by Chenhua 760 electrochemical workstation. The measured electronic resistivity was greater than 100 MΩ·cm, confirming that there is no electronic contribution to thermal conductivity in Cs2ZnI4, such as Figure 6 shown.
[0055] (2) Thermal conductivity test of polycrystalline Cs2ZnI4 material and single crystal Cs2ZnI4 material:
[0056] The sample preparation process of polycrystalline Cs2ZnI4 material is as follows: grind the polycrystalline Cs2ZnI4 ingot into Cs2ZnI4 powder, then put the Cs2ZnI4 powder into a graphite mold, apply an axial pressure of 50MPa using a hot pressing device, heat to 230°C and keep it for 1h, then release the pressure and cool to obtain a dense sheet (density exceeds 97% of the theoretical density). The sample preparation process of single crystal Cs2ZnI4 material is as follows: grind the final single crystal Cs2ZnI4 material into a uniform sheet structure.
[0057] The dependence of thermal conductivity of polycrystalline Cs2ZnI4 material and single crystal Cs2ZnI4 material on temperature is as follows Figure 7 As shown in the figure, both polycrystalline Cs2ZnI4 and single crystal Cs2ZnI4 materials have excellent thermal insulation properties, among which the thermal conductivity of polycrystalline Cs2ZnI4 at room temperature is 0.13W / m -1 K -1 ; The thermal conductivity of Cs2ZnI4 single crystal along the c-axis at room temperature is extremely low, only 0.11W / m - 1 K -1 The thermal conductivity of single crystals along the c-axis is lower than that of polycrystalline materials mainly because larger grains can reduce the scattering of grain boundaries and facilitate the propagation of phonons.
[0058] At the same time, the acoustic velocity of Cs2ZnI4 single crystals and polycrystals was measured at room temperature using an ultrasonic pulse receiver (Olympus-NDT) equipped with an oscilloscope (Keysight). Figure 8 As shown, the transverse sound velocity (νt) and longitudinal sound velocity (νl) along the c-axis are significantly lower than the sound velocity along the a-axis or b-axis. This is because the speed of the main heat carrier, the phonon, is significantly reduced.
[0059] Fig. 9 The temperature-dependent Raman spectrum of Cs2ZnI4 is shown, in which three peaks are visible. As the temperature increases, the frequency shifts to low frequencies, indicating that the phonon properties change from a soft state to a hard state, while the intensity increases, proving that the number of phonons increases as the temperature increases. The low phonon velocity and the low-frequency signals captured by Raman affect the propagation and scattering of phonons, so that the material shows low thermal conductivity.
[0060] In summary, the Cs2ZnI4 materials prepared in the present invention have excellent thermal insulation properties, and the thermal conductivity of the single crystal Cs2ZnI4 material at room temperature can be as low as 0.11 W / m -1 K -1 , is an ideal candidate for thermal insulation material.
[0061] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A polycrystalline Cs2ZnI4 material with low thermal conductivity, characterized in that: Prepared by the following method: CsI and ZnI2 are mixed and ground evenly, and then high-temperature melting, quenching and annealing are performed in sequence under a vacuum environment to obtain a polycrystalline Cs2ZnI4 material with low thermal conductivity; The thermal conductivity of the polycrystalline Cs2ZnI4 material at room temperature is not more than 0.17 W / m -1 K -1 .
2. A polycrystalline Cs2ZnI4 material with low thermal conductivity according to claim 1, characterized in that: The molar ratio of CsI to ZnI2 is 2:
1.
3. The low thermal conductivity polycrystalline Cs2ZnI4 material according to claim 1, characterized in that: The CsI and ZnI2 are mixed and ground evenly and then transferred into a quartz tube, which is then packaged after being evacuated to a pressure less than 6 Pa.
4. The low thermal conductivity polycrystalline Cs2ZnI4 material according to claim 1, characterized in that: The high temperature melting temperature is 650-700° C., and the high temperature melting time is 4-6 hours.
5. The low thermal conductivity polycrystalline Cs2ZnI4 material according to claim 1, characterized in that: The quenching medium is water; The annealing temperature is 200-300° C., and the annealing time is 24-72 hours.
6. A single crystal Cs2ZnI4 material with low thermal conductivity, characterized in that: Prepared by the following method: The polycrystalline Cs2ZnI4 material according to claim 1 is grown by a vertical gradient freezing method in a vacuum environment to obtain a single crystal Cs2ZnI4 material with low thermal conductivity.
7. A low thermal conductivity single crystal Cs2ZnI4 material according to claim 6, characterized in that: The specific steps of the vertical gradient freezing method are: The polycrystalline Cs2ZnI4 material is sealed in a quartz tube, and the quartz tube is placed in a vertical temperature gradient furnace, first melted at high temperature, and then cooled to room temperature, thereby obtaining a single crystal Cs2ZnI4 material.
8. A low thermal conductivity single crystal Cs2ZnI4 material according to claim 7, characterized in that: The high temperature melting temperature is 650-700°C, and the high temperature melting time is 4-6h; The cooling rate is 0.4-0.6°C / h.
9. A low thermal conductivity single crystal Cs2ZnI4 material according to claim 6, characterized in that: The single crystal Cs2ZnI4 material has anisotropy and its thermal conductivity at room temperature is no more than 0.17 W / m -1 K -1 .
10. Use of the Cs2ZnI4 material according to claim 1 or 6 in electronic equipment, thermoelectric materials or aerospace fields.
Citation Information
Cited By
Cs3Bi2I9 single-crystal material with double heat transfer operation modes as well as preparation method and application of Cs3Bi2I9 single-crystal material
CN121006598A
A Cs3Bi2I9 single crystal material with dual thermal transport behavior, its preparation method and application
CN121006598B